Nonsurfactant route of fatty alcohols decomposition for templating of mesoporous silica - Misran, Halina; Ramesh, Singh; Yarmo, Mohd Ambar (Elsevier, 2008)
Mesoporous silica with wormhole-like channel networks were successfully prepared in a direct synthesis method by a modified two-step base-acid catalyzed nonsurfactant carbon templating route at room temperature. This new method allows direct decomposition of palm oil derived fatty alcohols onto silica sources generating the required carbon template in situ to induce mesoporosity. Carbon templating using palm oil-derived fatty alcohols are renewable and environmental friendly. Furthermore, this method was carried out in a simple manner and the porosity of the resulting materials could be controlled successfully. The resulting materials had high surface area of 505 m(2)/g and pore volume of 1.4 mL/g, respectively. The median pore diameter estimated by the BJH method was at ca. 7.8 nm to 13 nm. Moreover, pH functionalized mesoporous silica materials exhibited stable absorbances for more than ten cycles at ca. 560 mu. (C) 2007 Elsevier Inc. All rights reserved.